2012
DOI: 10.1111/j.1460-9568.2012.08099.x
|View full text |Cite
|
Sign up to set email alerts
|

Phantom digit somatotopy: a functional magnetic resonance imaging study in forearm amputees

Abstract: Forearm amputees often experience non-painful sensations in their phantom when the amputation stump is touched. Cutaneous stimulation of specific stump areas may be perceived as stimulation of specific phantom fingers (stump hand map). The neuronal basis of referred phantom limb sensations is unknown. We used functional magnetic resonance imaging to demonstrate a somatotopic map of the phantom fingers in the hand region of the primary somatosensory cortex after tactile stump stimulation. The location and exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 36 publications
1
39
0
Order By: Relevance
“…For example, Björkman et al (2012) used functional magnetic resonance imaging (fMRI) during tactile stimulation of the residual limb and reported bilateral activation of the primary somatosensory cortex (SI), contralateral parietal and premotor cortices. However, they were not able to dissociate the neural activation induced by the stimulation of the residual limb from the percept of phantom sensations as they might have activated inputs from the residual limb to the brain region that formerly represented the amputated limb and they did not assess ratings of evoked phantom sensations.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Björkman et al (2012) used functional magnetic resonance imaging (fMRI) during tactile stimulation of the residual limb and reported bilateral activation of the primary somatosensory cortex (SI), contralateral parietal and premotor cortices. However, they were not able to dissociate the neural activation induced by the stimulation of the residual limb from the percept of phantom sensations as they might have activated inputs from the residual limb to the brain region that formerly represented the amputated limb and they did not assess ratings of evoked phantom sensations.…”
Section: Introductionmentioning
confidence: 99%
“…In a case-study report, it was shown that when observing actions outside of their motor repertoire, amputees recruit areas outside of the expected left parietofrontal system (attributed to the mirror neuron system), additionally areas including the right temporoparietal junction (attributed to the mentalizing system (Van Overwalle et al, 2009, Aziz-Zadeh et al, 2012)). Other studies have also shown motor activation expanded to the parietal areas which correlates with phantom sensations (Bjorkman et al, 2012). While none of our participants reported lingering phantom sensations, in this study activation is best aligned to concerns in motor planning beyond sensation.…”
Section: Discussionmentioning
confidence: 90%
“…Thus, the remapping of S1 does not necessarily reflect changed circuitry in S1. Fourth, some amputees develop distinct patches of skin on their limb stump, stimulation of which results in a percept projected to individual digits on the phantom hand and activation in the corresponding digit representation in S1 (Bjorkman et al, 2012). As might be expected, then, electrical stimulation of deafferented regions of S1 in human amputees evokes sensations on the phantom limb rather than on the invading body regions (Ojemann and Silbergeld, 1995; Woolsey et al, 1979).…”
Section: Plasticitymentioning
confidence: 99%